Cadherin-12 Regulates Neurite Outgrowth Through the PKA/Rac1/Cdc42 Pathway in Cortical Neurons - Guo, Beibei; Qi, Mengwei; Huang, Shuai; Zhuo, Run; Zhang, Wenxue; Zhang, Yufang; Xu, Man; Liu, Mei; Guan, Tuchen; Liu, Yan (Frontiers in Cell and Developmental Biology, 2021)
Cadherins play an important role in tissue homeostasis, as they are responsible for cell-cell adhesion during embryogenesis, tissue morphogenesis, and differentiation. In this study, we identified Cadherin-12 (CDH12), which encodes a type II classical cadherin, as a gene that promotes neurite outgrowth in an in vitro model of neurons with differentiated intrinsic growth ability. First, the effects of CDH12 on neurons were evaluated via RNA interference, and the results indicated that the knockdown of CDH12 expression restrained the axon extension of E18 neurons. The transcriptome profile of neurons with or without siCDH12 treatment revealed a set of pathways positively correlated with the effect of CDH12 on neurite outgrowth. We further revealed that CDH12 affected Rac1/Cdc42 phosphorylation in a PKA-dependent manner after testing using H-89 and 8-Bromo-cAMP sodium salt. Moreover, we investigated the expression of CDH12 in the brain, spinal cord, and dorsal root ganglia (DRG) during development using immunofluorescence staining. After that, we explored the effects of CDH12 on neurite outgrowth in vivo. A zebrafish model of CDH12 knockdown was established using the NgAgo-gDNA system, and the vital role of CDH12 in peripheral neurogenesis was determined. In summary, our study is the first to report the effect of CDH12 on axonal extension in vitro and in vivo, and we provide a preliminary explanation for this mechanism.